Diffusion of innovations - Rogers, Everett M. (New York : Free Press, 2003)
This references concerns the history of the spread of new ideas. It explains how inventions are almost always perceived as uncertain or even risky. To overcome this, most people seek out others like themselves who have already adopted the new idea. The diffusion process, then, is most often shaped by a few individuals who spread the word amongst their circle of acquaintances, a process that typically takes months or years. But there are exceptions: use of the Internet in the 1990s, for instance, may have spread more rapidly than any other innovation in human history - and it continues to influence the very nature of diffusion by decreasing the significance of physical distance between people. As thought-provoking as it is instructive, this fully updated, widely acclaimed work of scholarship is itself a great idea that continues to spread.
Includes bibliographical references (pages 477-535) and indexes.
Keywords: Diffusion of innovations; Diffusion of innovations -- Study and teaching -- History